Production of orbitally excited charm mesons in semileptonic B decays - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1997)
A sample of 3.6 million hadronic Z decays recorded between 1991 and 1995 with the ALEPH detector at LEP is used to investigate semileptonic decays of B mesons into final states involving orbitally excited charm mesons. Topological vertex criteria are used to search for decays involving narrow D** states as well as wide D** resonances and non-resonant D(*)π final states. The sum of the branching ratios for these processes is measured to be ${⤪ Br}({⩈erline {⤪ B}}⌝ghtarrow {⤪ D}≪ ⫑l^{-}{⩈erline v}) + {⤪ Br}({⩈erline {⤪ B}}⌝ghtarrow {⤪ D}^{⇒t}≪ ⫑l^{-}{⩈erline v})↦op =(2.26 pm 0.29({⤪ stat}) pm 0.33({⤪ syst}))%,$which accounts for a significant fraction of the deficit between inclusive measurements and the sum of exclusive semileptonic B decay modes.